Pengembangan LKPD Matematika dengan Pendekatan Contextual Teaching and Learning Pada Kelas V SD - Cinta, Amanda Clara; Syutaridho, Syutaridho (Universitas Muhammadiyah Palembang, 2024)
This research began by finding that students lack mathematical problem-solving, critical thinking, and curiosity skills, due to their difficulty applying mathematical principles in real-world situations. They have difficulty applying what they have learned in real life, thus limiting their ability to solve math difficulties. Learner Worksheets (LKPD) are not designed to allow learners to actively develop their own understanding. The purpose of this study is to develop authentic, practical, and successful LKPD using CTL (Contextual Teaching and Learning) approach to increase students' participation in problem solving in grade V elementary school. This research follows Plomp's development paradigm, which consists of three stages: initial investigation, prototype development, and assessment. The result of this research is a validated, practical, and effective mathematics LKPD with CTL method to be used in grade V elementary school